LEARNING FROM HOME IN INDONESIAN ELEMENTARY SCHOOL - Andarini Permata Cahyaningtyas; Jupriyanto Jupriyanto (Universitas Pendidikan Indonesia, 2022)
Online learning has become the only alternative in many countries during the Covid-19 pandemic, including Indonesia. The study aimed to find about the online learning platform used by Indonesian elementary school teachers and what kind of problems they experienced during the outbreak in Semarang, Central Java. The research method used is the survey method. The survey was conducted online among 160 elementary school teachers, from 47 state and private schools to find fact what kind of online learning apps they used and the problem they have to experience while conducting online learning during the pandemic. According to the result of the study, we can conclude that there were 18 platforms used by teachers to conduct online learning during the pandemic. Therefore, teachers had to experience eight obstacles that most of the problems came from the internet connection, learning facilities, and the attitude of the students and parents toward online learning. From this result, teachers are expected to have a better understanding in carrying out the online learning, and find a better solution in order to solve the problems.